The experimental study of the immunomodulating action of Semax and Selank on the model of "social" stress - Yasenyavskaya A.L; Samotrueva M.A; Myasoedov N.F; Andreeva L.A (Sciendo, 2022)
This study is devoted to the experimental study of the immunocorrecting action of Semax (Met-Glu-His-Phe-Pro-Gly-Pro) and Selank (Thr-Lys-Pro-Arg-Pro-Gly-Pro) on the model of "social" stress formed as a result of sensory contact and inter-confrontation. Functional activity of the immune system of laboratory animals was assessed on the basis of standard immunopharmacological tests: delayed-type hypersensitivity reaction (DTH), direct agglutination test (DAT), latex test for studying the phagocytic activity of peripheral blood neutrophils, and evaluation of changes in the leukocyte formula. As a result of the experiment, it was found that, under the influence of "social" stress, changes in the immune response are multidirectional, which confirms the theory of "immune disbalance" under the action of stressors. As a result of studying the influence of Semax and Selank on the model of "social" stress, it was found that the drug proved to be an effective corrector, restoring the cellular and humoral immunogenesis reactions, the phagocytic activity of neutrophils, which indicates the presence of immunomodulating properties, and emphasizes the need for further studies in this scientific direction. This study expands the scientific research base in the field of immunoreaction under stress-induced conditions with the aim of further developing a pharmacological strategy for correcting the revealed disorders by means of substances of a neuropeptide structure.